Effect of greengram + sesame intercropping system on growth, nodulation and biomass production of green gram in Central India - Sarvesh Kumar Shukla; H.S. Kushwaha (Annals of Agricultural Research, 2024)
A field experiment was carried out at Mahatma Gandhi Chitrakoot Gramodaya Vishwavidyalaya, Chitrakoot, Satna (M.P.) during the kharif season of 2017-18 and 2018-19 to investigate the impact of green gram + sesame intercropping system on the growth, nodulation, and biomass production of green gram in Central India. Result revealed that sole greengram (30 cm) recorded significantly higher growth characters, i.e. plant height, branches/plant, nodulation parameters viz. nodules/plant, fresh and dry weight of nodules/plant and biomass yield i.e. grain yield, stover yield and biological yield over all the greengram + sesame intercropping systems. However, among the intercrops treatment, Greengram + Sesame (1:1 ratio alternate of 20 cm)] obtained significantly higher plant height (46.22 and 46.84 cm) at harvest and branches/plant of 6.15 and 6.3 at 35 DAS and 6.35 and 6.52 at harvest during two consecutive years. Nodules per plant (19.85 and 21.03), fresh weight of nodules (1102.2 and 1155.93 mg/plant) and dry weight of nodules (392.59 and 415.9 mg/ plant) were found significantly greater under Greengram + Sesame (6:3 ratio 120/60 cm alternate of 20 cm) during two respective years. While, biomass parameters viz. grain yield (647 and 771 kg/ha), stover yield (1409 and 1610 kg/ha) and biological yield (2056 and 2382 kg/ha) were obtained significantly superior under Greengram + Sesame (2:1 ratio 40/20 cm alternate of 20 cm) than that of rest of the greengram + sesame intercropping system.